PENDAMPINGAN PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL INKUIRI TERBIMBING BERBASIS ICT BAGI GURU SMP DI LINGKUNGAN PONDOK PESANTREN SALAFIYAH SYAFI’IYAH IBRAHIMY SITUBONDO - Dian Noer Asyari (LP2M Universitas Ibrahimy, 2019)
The availability of ICT-based learning tools is one of the supports for the creation of classes that implement E-learning. The learning process can occur if there are at least two main elements, namely: (1) people who learn, and (2) learning resources. Learning resources include people (resource persons), tools (hardware), materials (software), environment (background, settings) and others. Learning tools are one type of learning resource and become an element that has a very important role in e-learning. There is no e-larning without the availability of learning tools, so the ability of teachers to develop ICT-based learning tools becomes very important. This learning device is often also called an internet-based learning device or online learning device. Three main characteristics of this learning tool include: (1) presenting multi media, (2) preparing, processing and presenting information, and (3) hyperlinks. The nature of this online learning tool has the advantage that it can be accessed anytime and anywhere as long as it has internet access, so that the teacher has the ability to develop ICT-based learning tools. These characteristics make the source of learning tools very rich, and the availability of appropriate ICT-based guided inquiry learning model tools is very much needed as a relevant learning resource.